Quality assessment of pasteurized fresh milk produced by the Iloilo Federation of Dairy Cooperatives (IFEDCO) - Salarda, Patrick Esico (Miagao, Iloilo School of Technology, U.P. Visayas, 2010)
The pasteurized fresh milk produced by Iloilo Federation of Dairy Cooperatives at Tigbauan, Iloilo was assessed for its quality attributes.
Sotech thesis.
Keywords: Fresh milk; Pasteurization